(3YhGQa GdeYGQas - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje TCfg aSHMGf ef YRJ eYQaJg dhdG JYQjag Ke CdHS bdhH Cgd GdUahI hCDda CHhGHkG ai GdMbGFb hGddBOGH s
(3BNQgG (B:s
(3Ke jfGOi LHQjd ai GdSeGA (B: (3Ef Gddg bO CMH adGfkG ajMHI Cgd GdSeGA , hjhVY dg GdbHhd ai GdCQV BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B197s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe EHQGgje Hf GdLHQ GdUMadi s
(3hYdi GdfSNI JedcGJ CbOegG SfI (B987(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs